Notch Signaling Mediates TNF-α-Induced IL-6 Production in Cultured Fibroblast-Like Synoviocytes from Rheumatoid Arthritis - Zhijun Jiao; Wenhong Wang; Jie Ma; Shengjun Wang; Zhaoliang Su; Huaxi Xu (Clinical and Developmental Immunology)
It has been reported that Notch family proteins are expressed in synovium tissue and involved in the proliferation of synoviocyte from rheumatoid arthritis (RA). The aim of this paper was to investigate whether Notch signaling mediated TNF-α-induced cytokine production of cultured fibroblast-like synoviocytes (FLSs) from RA. Exposure of RA FLSs to TNF-α (10 ng/ml) led to increase of Hes-1, a target gene of Notch signaling, and a marked upregulation of Notch 2, Delta-like 1, and Delta-like 3 mRNA levels. Blockage of Notch signaling by a γ-secretase inhibitor (DAPT) inhibited IL-6 secretion of RA FLSs in response to TNF-α while treatment with recombinant fusion protein of Notch ligand Delta-like 1 promoted such response. TNF-α stimulation also induced IL-6 secretion in OA FLSs; however, the Hes-1 level remained unaffected. Our data confirm the functional involvement of Notch pathway in the pathophysiology of RA FLSs which may provide a new target for RA therapy.